EU energy in figures: statistical pocketbook 2014 (Luxembourg, 2014)
"The energy sector is one of the pillars of growth, competitiveness and development in modern economies. To keep up with the permanent transformation of the energy sector in Europe we need to have a continuous supply of accurate and up-to-date data. This publication provides an overview of the most relevant annual energy related statistics for the European Union as a whole and for each one of its Member States"